Sociodemographic and Occupational Factors Associated With Burnout: A Study Among Frontline Healthcare Workers During the COVID-19 Pandemic - Aljabri, Duaa; Alshatti, Fatimah; Alumran, Arwa; Al-Rayes, Saja; Alsalman, Deema; Althumairi, Arwa; Al-kahtani, Nouf; Aljabri, Mohammad; Alsuhaibani, Shaheed; Alanzi, Turki (Frontiers in Public Health, 2022)
Purpose: To describe the prevalence of burnout among frontline healthcare workers (HCWs) during the COVID-19 pandemic and the associated sociodemographic and occupational factors. Methods: A cross sectional survey study was carried out to study HCWs burnout using the 19-item Full Copenhagen Burnout Inventory (CBI) that includes personal, work, and patient-related burnout subscales. Bivariate analysis was used to test for associations and p < 0.05 was considered statistically significant. Results: A total of 207 responses received; where the mean score of personal burnout was 67.23, the mean of work-related burnout was 61.38, and the mean of patient-related burnout was 54.55. Significant associations were found; where female HCWs, those working in rotating day-and-night shifts, working more than 55-hours per week, and who had their shift time and hours changed during the pandemic, had higher levels of personal and work-related burnout (P<0.05). Patient-related burnout was higher among those who were single (divorced or separated), nurses, non-Citizens, those with fewer years of experience, and who were infected by COVID-19 and have been quarantined (P<0.05). Age was not a significant factor of burnout in any of the CBI subscales. Conclusions: There is a prevalent level of burnout among frontline HCWs during the COVID-19 pandemic. Findings highlight key sociodemographic and occupational factors affecting burnout; suggesting urgent strategies by the healthcare system to focus on those factors when planning psychological interventions to promote HCWs wellness in facing future waves of the pandemic.